2008
DOI: 10.1007/s00417-008-0765-z
|View full text |Cite
|
Sign up to set email alerts
|

Ocular toxicity of intravitreous adalimumab (Humira) in the rabbit

Abstract: Escalating doses of intravitreous adalimumab in rabbit eyes caused no detectable functional or structural ocular toxicity up to a dose of 0.50 mg. Administration of 1.0 mg in 0.1 ml was associated with an inflammatory reaction and retinal necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
0
30
1
3
Order By: Relevance
“…In the current study we did not find any toxic effect, even though we used a fivefold greater dose (5 mgr/0.1 ml) than the 1.0 mg/ 0.1 ml used by Manzano et al [28] which demonstrated toxic effects. Differences in the composition of the administered drug may explain the differences observed in high-dose toxicity.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In the current study we did not find any toxic effect, even though we used a fivefold greater dose (5 mgr/0.1 ml) than the 1.0 mg/ 0.1 ml used by Manzano et al [28] which demonstrated toxic effects. Differences in the composition of the administered drug may explain the differences observed in high-dose toxicity.…”
Section: Discussioncontrasting
confidence: 64%
“…A recent study in the literature by Manzano et al [28], investigating intravitreal toxicity of adalimumad in rabbit eyes, concluded that doses 0.2 and 0.5 mg/0.1 ml do not demonstrate any toxic effects; however, administration of 1.0 mg/0.1 ml was associated with an inflammatory reaction in two animals and retinal necrosis in one animal out of the three tested [28]. In the current study we did not find any toxic effect, even though we used a fivefold greater dose (5 mgr/0.1 ml) than the 1.0 mg/ 0.1 ml used by Manzano et al [28] which demonstrated toxic effects.…”
Section: Discussionmentioning
confidence: 98%
“…One study recently demonstrated the safety profile of intravitreal injections of various doses of adalimumab in rabbits. Their results showed normal retinal examination in eyes having received injections of balanced salt solution (BSS), 0.25 or 0.50 mg adalimumab; however, 1 mg adalimumab induced inflammatory changes, retinal histopathological alterations and significant ERG reduction [102] . In summary, most studies suggest a dose-dependent retinal toxicity profile for intravitreal anti-TNF mAbs, and further evaluation should determine the exact safe dosage for each drug.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Moreover, intravitreal injections of infliximab may lead to serious intraocular inflammation. 21 On the other hand, IVA did not lead to retinal damage in animal models at a dose of 0.5 mg in one study 22 and up to 5 mg in another study. 23 No information is available on the stability and efficacy of reconstituted or aliquoted adalimumab for multiple use to date.…”
Section: Discussionmentioning
confidence: 92%